Estradiol and the Development of the Cerebral Cortex: An Unexpected Role? - Denley, Matthew C. S.; Gatford, Nicholas J. F.; Sellers, Katherine J.; Srivastava, Deepak P. (Frontiers in Neuroscience, 2018)
The cerebral cortex undergoes rapid folding in an “inside-outside” manner during embryonic development resulting in the establishment of 6 discrete cortical layers. This unique cytoarchitecture occurs via the coordinated processes of neurogenesis and cell migration. In addition, these processes are fine-tuned by a number of extracellular cues, which exert their effects by regulating intracellular signaling pathways. Interestingly, multiple brain regions have been shown to develop in a sexually dimorphic manner. In many cases, estrogens have been demonstrated to play an integral role in mediating these sexual dimorphisms in both males and females. Indeed, 17β-estradiol, the main biologically active estrogen, plays a critical organizational role during early brain development and has been shown to be pivotal in the sexually dimorphic development and regulation of the neural circuitry underlying sex-typical and socio-aggressive behaviours in males and females. However, whether and how estrogens, and 17β-estradiol in particular, regulate the development of the cerebral cortex is less well understood. In this review, we outline the evidence that estrogens are not only present but are engaged and regulate molecular machinery required for the fine-tuning of processes central to the cortex. We discuss how estrogens are thought to regulate the function of key molecular players and signaling pathways involved in corticogenesis, and where possible, highlight if these processes are sexually dimorphic. Collectively, we hope this review highlights the need to consider how estrogens may influence the development of brain regions directly involved in the sex-typical and socio-aggressive behaviours as well as development of sexually dimorphic regions such as the cerebral cortex.